Identification of Gingival Crevicular Fluid Sampling, Analytical Methods, and Oral Biomarkers for the Diagnosis and Monitoring of Periodontal Diseases: A Systematic Review - Majeed, Z.N.; Philip, K.; Alabsi, A.M.; Pushparajan, S.; Swaminathan, D. (Hindawi Publishing Corporation, 2016)
Background. Several studies in the last decades have focused on finding a precise method for the diagnosis of periodontal disease in its early stages. Aim. To evaluate from current scientific literature the most common and precise method for gingival crevicular fluid (GCF) sample collection, biomarker analytical methods, and the variability of biomarker quantification, even when using the same analytical technique. Methodology. An electronic search was conducted on in vivo studies that presented clinical data on techniques used for GCF collection and biomarker analysis. Results. The results showed that 71.1%, 24.7%, and 4.1% of the studies used absorption, microcapillary, and washing techniques, respectively, in their gingival crevicular fluid collection. 73.1% of the researchers analyzed their samples by using enzyme-linked immunosorbent assay (ELISA). 22.6%, 19.5%, and 18.5% of the researchers included interleukin-1 beta (IL-1β), matrix metalloproteinase-8 (MMP-8), and tumor necrosis factor-alpha (TNF-α), respectively, in their studies as biomarkers for periodontal disease. Conclusion. IL-1β can be considered among the most common biomarkers that give precise results and can be used as an indicator of periodontal disease progression. Furthermore, paper strips are the most convenient and accurate method for gingival crevicular fluid collection, while enzyme-linked immunosorbent assay can be considered the most conventional method for the diagnosis of biofluids.